Top management team characteristics and firm internationalization: The moderating role of the size of middle managers. Issue 1 (February 2018) - Li, Peng-Yu
Highlights: This study shed light into the information-process perspective in the firms' internationalization process. MMs provide information processing capabilities that help TMTs in the strategic decision-making process. The findings indicate an inverted U-shaped relationship between TMT tenure and firm internationalization. A positive relationship exists between TMT international experience and firm internationalization. MM size positively enhances the inverted U-shaped relationship between TMT tenure and firm internationalization. Abstract: This paper examines the influence of the top management teams' (TMTs) characteristics, including tenure and international experience, on the degree of firm internationalization. In addition, this study explores the moderating effect of the size of middle managers (MMs) on the relationship between the TMT characteristics and the degree of firm internationalization. This study use the information-process perspective to emphasize that MMs provide information processing capabilities that assist TMTs as they cope with the high information-processing demands of the strategic decision-making process in international markets. We test the hypotheses using a sample of listed manufacturing firms in the electro-optical and textile industries during the 2006–2010 period. The findings indicate that TMT tenure has an inverted U-shaped relationship with firm internationalization and TMT international experience has a positively affect the firm internationalization. Furthermore, we find that large MM size positively enhances the inverted U-shaped relationship between TMT tenure and firm internationalization.